POLA BANGUNAN LEUIT, SAUNG LISUNG, DAN GOAH MASYARAKAT SUNDA KASEPUHAN CIPTAGELAR DALAM PENGELOLAAN PANGAN - Afina Nisa Aulia; Gregorius Prasetyo Adhitama (Serat Rupa: Journal of Design, 2021)
As a farming community who still applies ancestral rules, the Sundanese Kasepuhan Ciptagelar people have their own rules regarding food processing, starting from storing rice in the leuit (barn), pounding rice in saung lisung, to cooking rice in goah (cooking area). This community also never lacks food, even has sufficient food supplies for the next few years, which is why the main objective of this research is to see the relationship between the use of leuit, saung lisung, and goah with the success of the Kasepuhan Ciptagelar community in managing food, especially in terms of building layout. Based on these objectives, this research is included in ethnographic research with qualitative research methods. The data in this study were obtained from the results of site-plan observations of the Sundanese Kasepuhan Ciptagelar traditional village, the distance between buildings, and the total number of buildings. The data then analyzed using Edward Relph's theory of space and distance, which states that the distance of each building represents its own identity and meaning which is based on human understanding of space or the distance from the inhabited environment. The analysis of the position and distance of the building was then linked to the success of the food management of the Kasepuhan Ciptagelar community using the interpretive analysis method. The results of the study found that the entire Kasepuhan Ciptagelar village is a large area so that it is divided into several building clusters which are quite far apart from each other. Even so, because the three objects of this research are an integrated unit that cannot be separated, then they will always exist in each of the smallest and most isolated clusters. Thus, each cluster has at least one leuit complex where rice is stored, one saung lisung for pounding rice, and each house has a goah for cooking rice. The existence of these three types of buildings makes each cluster sovereign in terms of food where they each have facilities to store rice, pound rice, and cook rice.